A molecular reconstruction of holarctic Heligmosomidae reveals a new species of Heligmosomoides (Nematoda: Heligmosomidae) in Peromyscus maniculatus (Neotominae) from Canada. Issue 1 (31st December 2022) - Alnaqeb, Haitham; Greiman, Stephen E.; Vandegrift, Kurt J.; Campbell, Mariel L.; Meagher, Shawn; Jiménez, F. Agustín
Abstract : A new species of Heligmosomoides Hall, 1916 is proposed for nematodes collected from deer mice, Peromyscus maniculatus, in western Canada. The unequivocal diagnostic character for this species is the presence of two internal bursal membranes. Only four species, Heligmosomoides bullosus, Heligmosomoides douglasi, Heligmosomoides montanus and Heligmosomoides vandegrifti, are characterized as possessing a single internal bursal membrane. The genetic distance between Heligmosomoides bibullosus sp. nov., and its putative sister clade Heligmosomoides vandegrifti is congruent with their geographic separation by the mountain range of the Rockies and 4000 km; both morphological difference as well as geography and genetic distance suggest isolation among the two species. Further, H. bibullosus sp. nov. infects deer mice ( P. maniculatus ) whereas H . vandegrifti is frequently collected in white-footed mice ( P. leucopus ). Finally, this study supports the taxonomic importance of the monodelphic/didelphic condition as a diagnostic trait within the family, the paraphyly of Heligmosomoides, and reveals undocumented diversity of Heligmosomoides in Nearctic rodents of the Neotominae. The present taxon is the third species in members of this subfamily of rodents. http://www.zoobank.org/urn:lsid:zoobank.org:pub:DE78368D-2CDE-4F9D-AB85-A3CE20D957F4